2018
DOI: 10.1016/j.jsxm.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Vaginal Laxity—Prevalence, Impact, and Associated Symptoms in Women Attending a Urogynecology Clinic

Abstract: Introduction Vaginal laxity is increasingly recognized as an important condition, although little is known regarding its prevalence and associated symptoms. Aim To report the prevalence of self-reported vaginal laxity in women attending a urogynecology clinic and investigate its association with pelvic floor symptoms and female sexual dysfunction. Method Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 7 publications
3
39
0
1
Order By: Relevance
“…13 Moreover, VL has been reported by physicians as the foremost complaint made to them by patients in the postpartum setting. 8,9 Healthy sexual functioning is an integral part of women's overall general health, and VL in women often generates dissatisfaction with physical sensation and sexual function. 9,22 The application of energy-based devices for improving VL, and furthermore the subsequent related positive Noteworthy is the prolongation of positive outcomes of both VHI improvement and self-reported GRAS-VL responses, with results being maintained and/or further improved to 4 months after final treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Moreover, VL has been reported by physicians as the foremost complaint made to them by patients in the postpartum setting. 8,9 Healthy sexual functioning is an integral part of women's overall general health, and VL in women often generates dissatisfaction with physical sensation and sexual function. 9,22 The application of energy-based devices for improving VL, and furthermore the subsequent related positive Noteworthy is the prolongation of positive outcomes of both VHI improvement and self-reported GRAS-VL responses, with results being maintained and/or further improved to 4 months after final treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 Although underreported, diminished vaginal elasticity and laxity affect 25%-45% of premenopausal women; they have been cited as the most dominant physical changes felt by patients and discussed with physicians following vaginal delivery, with parity being considered a significant risk factor. 2,8,9 Furthermore, VL may worsen with multiparity, application of forceps, delivery of a large fetus, weight fluctuations, and connective tissue changing due to aging. 10,11 Treatments for VL include both surgical and noninvasive options.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of vaginal laxity has started to be systematically addressed only recently, with 2 studies showing that 28e40% of surveyed women (patients in urogynecological clinics) suffered from a degree of vaginal laxity that negatively affects their quality of life (QoL). 1,2 In the study by Dietz et al, 2 the women rated the problem a score of 5.7 on a 0-10 Visual Analog Scale (VAS) scale. In the study by Campbell et al, 1 48% of surveyed women reported symptoms of vaginal laxity and almost 90% of these women reported vaginal laxity as a presenting a problem.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the study by Dietz et al, 2 the women rated the problem a score of 5.7 on a 0-10 Visual Analog Scale (VAS) scale. In the study by Campbell et al, 1 48% of surveyed women reported symptoms of vaginal laxity and almost 90% of these women reported vaginal laxity as a presenting a problem. Physicians have also started to recognize vaginal laxity as a bothersome symptom in their patientsePauls et al 3 published a survey of urogynecologists' perception of vaginal laxity issues.…”
Section: Introductionmentioning
confidence: 99%
“…As aging progresses, reductions in vaginal wall elasticity and lubrication are common. Subsequently, sensation during intercourse is decreased and vaginal dryness or irritation occurs [15,16]. Therefore, vaginal laxity and dryness could be one of the causes of FSD [13,17].…”
Section: Introductionmentioning
confidence: 99%